2021
DOI: 10.1007/s15010-021-01662-1
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for early readmission after hospitalization for SARS-CoV-2 infection: results from a retrospective cohort study

Abstract: Purpose We aim to assess risk factors related to early readmission in previous hospitalized patients with COVID-19. Methods We analyzed a retrospective cohort of patients with laboratory-confirmed COVID-19 admitted to Vall d'

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
3
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 30 publications
1
13
3
2
Order By: Relevance
“…Myocardial injury with COVID-19 has been extensively reported, with rates widely varying depending upon the population studied. 4 The underlying causes are numerous and include but are not limited to myocarditis, 22 acute coronary syndrome (myocardial infarction type 1), 17 demand ischemia (myocardial infarction type 2), 25 , 32 , 33 , 34 , 35 multisystem inflammatory syndrome in children (MIS-C) and multisystem inflammatory syndrome in adults (MIS-A), 20 , 21 , 24 takotsubo/stress cardiomyopathy, 36 , 37 cytokine storm, 34 acute cor pulmonale resulting from macropulmonary or micropulmonary emboli, 23 , 25 myocardial injury from chronic conditions like pre-existing heart failure, 38 , 39 , 40 , 41 and acute viral infection unmasking subclinical heart disease. 38 Because 1 or more of these etiologies may coexist, it can sometimes be challenging to identify a specific underlying cause.…”
Section: Description Of Pathwaymentioning
confidence: 99%
“…Myocardial injury with COVID-19 has been extensively reported, with rates widely varying depending upon the population studied. 4 The underlying causes are numerous and include but are not limited to myocarditis, 22 acute coronary syndrome (myocardial infarction type 1), 17 demand ischemia (myocardial infarction type 2), 25 , 32 , 33 , 34 , 35 multisystem inflammatory syndrome in children (MIS-C) and multisystem inflammatory syndrome in adults (MIS-A), 20 , 21 , 24 takotsubo/stress cardiomyopathy, 36 , 37 cytokine storm, 34 acute cor pulmonale resulting from macropulmonary or micropulmonary emboli, 23 , 25 myocardial injury from chronic conditions like pre-existing heart failure, 38 , 39 , 40 , 41 and acute viral infection unmasking subclinical heart disease. 38 Because 1 or more of these etiologies may coexist, it can sometimes be challenging to identify a specific underlying cause.…”
Section: Description Of Pathwaymentioning
confidence: 99%
“…All three study from Spain use logistic regression for their research, and the data sizes are 7,137, 1,368, and 629, respectively. Age, age-adjusted Charlson comorbidity index score, chronic obstructive pulmonary disease (COPD), asthma, hemoglobin level at admission, ground-glass opacification at admission, and glucocorticoid treatment are identified by Ramos-Martínez et al ( 24 ), immunocompromised patients, hypertensive patients, and fever during the 48 h prior to discharge by Parra et al ( 23 ), while prior diagnosis of heart failure, length of stay during index admission >13 days, treatment with corticosteroids and developing pulmonary thromboembolism are identified by Kirkegaard et al ( 16 ).…”
Section: Readmission Risk Factors Post Covid-19 Admissionmentioning
confidence: 99%
“…The reasons for hospital readmissions were progression of lung involvement due to COVID-19 pneumonia, respiratory failure, unspecified infectious diseases, cardiovascular diseases, venous thrombosis, and gastrointestinal diseases. Other studies evaluated readmissions over a period of 60 days after confirmed infection with SARS-CoV-2; the proportion of readmission was 4.5–19.9% [ 65 , 66 , 67 ]. The most common causes of admissions were respiratory failure, progression of inflammatory changes after previous COVID-19 infection, venous thromboembolism, and various infective complications.…”
Section: Discussionmentioning
confidence: 99%